White matter microstructure predicts longitudinal social cognitive outcomes after paediatric traumatic brain injury: a diffusion tensor imaging study. Issue 4 (7th August 2017) - Ryan, N. P.; Genc, S.; Beauchamp, M. H.; Yeates, K. O.; Hearps, S.; Catroppa, C.; Anderson, V. A.; Silk, T. J.
Abstract : Background: Deficits in social cognition may be among the most profound and disabling sequelae of paediatric traumatic brain injury (TBI); however, the neuroanatomical correlates of longitudinal outcomes in this domain remain unexplored. This study aimed to characterize social cognitive outcomes longitudinally after paediatric TBI, and to evaluate the use of sub-acute diffusion tensor imaging (DTI) to predict these outcomes. Methods: The sample included 52 children with mild complex-severe TBI who were assessed on cognitive theory of mind (ToM), pragmatic language and affective ToM at 6- and 24-months post-injury. For comparison, 43 typically developing controls (TDCs) of similar age and sex were recruited. DTI data were acquired sub-acutely (mean = 5.5 weeks post-injury) in a subset of 65 children (TBI = 35; TDC = 30) to evaluate longitudinal prospective relationships between white matter microstructure assessed using Tract-Based Spatial Statistics and social cognitive outcomes. Results: Whole brain voxel-wise analysis revealed significantly higher mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) in the sub-acute TBI group compared with TDC, with differences observed predominantly in the splenium of the corpus callosum (sCC), sagittal stratum (SS), dorsal cingulum (DC), uncinate fasciculus (UF) and middle and superior cerebellar peduncles (MCP & SCP, respectively). Relative to TDCs, children with TBI showed poorer cognitive ToM, affective ToM and pragmatic language at 6-months post-insult, and those deficits were related to abnormal diffusivity of the sCC, SS, DC, UF, MCP and SCP. Moreover, children with TBI showed poorer affective ToM and pragmatic language at 24-months post-injury, and those outcomes were predicted by sub-acute alterations in diffusivity of the DC and MCP. Conclusions: Abnormal microstructure within frontal-temporal, limbic and cerebro-cerebellar white matter may be a risk factor for long-term social difficulties observed in children with TBI. DTI may have potential to unlock early prognostic markers of long-term social outcomes.